Anomalous Nernst effect and field-induced Lifshitz transition in the Weyl semimetals TaP and TaAs - Caglieris, Federico; Wuttke, Christoph; Sykora, S.; Suess; Shekhar, Chandra; Felser, Claudia; Buechner, B.; Hess, Christian (Physical Review B, 2018)
The discovery of Weyl fermions in transition-metal monoarsenides/phosphides without inversion symmetry represents an exceptional breakthrough in modern condensed matter physics. However, exploring the inherent nature of these quasiparticles is experimentally elusive because most of the experimental probes rely on analyzing Fermi arc topology or controversial signatures such as the appearance of the chiral anomaly and the giant magnetoresistance. Here, we show that the prototypical type-I Weyl semimetals TaP and TaAs possess a giant anomalous Nernst signal with a characteristic saturation plateau beyond a critical field which can be understood as a direct consequence of the finite Berry curvature originating from the Weyl points. Our results thus promote the Nernst coefficient as an ideal bulk probe for detecting and exploring the fingerprints of emergent Weyl physics.
CRIS-Team Scopus Importer:2022-04-14